OPTIMIZING LISTENING SKILLS TO IMPROVE THE TOEFL SCORE OF STAIN PEKALONGAN STUDENTS - Riskiana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
The fact that the students have problems in the three micro-skills of listening namely recognizing the English stress patterns, the reduced forms of words, and words boundaries and that the teachers never teach the students how to listen have made them get low TOEFL scores on listening section. This research aims at: (1) finding out whether optimizing listening skills can improve the students’ TOEFL scores on listening; and (2) describing the class situation during the teaching of toefl listening by optimizing listening skills. This action research is conducted in two cycles each of which is divided into planning, acting, observing, and reflecting. There are two kinds of data. The qualitative data taken from observation, interview, and questionnaire are analyzed by using Constant Comparative Method. The quantitative data taken from the pre-test in the pre-research, post-test in cycle 1, and post-test in cycle 2 are analyzed by using descriptive statistics. The subjects of the research are the STAIN Pekalongan students taking English 3 class, the TOEFL Preparation Class, in the Academic Year 2014/2015. The result of the research shows that: (1) teaching toefl listening section by optimizing listening skills is able to overcome the students’ problems in the three micro-skills of listening and consequently improve the students’ TOEFL scores on listening. Their average scores improve from 101 in the pre-test to 118 in the post-test of cycle 1 and 129 in the post-test of cycle 2; (2) The class situation is attractive and the students are actively involved in the various activities done during the teaching and learning process. In line with the success of optimizing listening skills in teaching TOEFL listening, it is suggested that teachers should examine their students’ listening problems so as to be able to teach them what they need in listening to English.